2015
DOI: 10.1002/hep.28300
|View full text |Cite
|
Sign up to set email alerts
|

A functional classification of ABCB4 variations causing progressive familial intrahepatic cholestasis type 3

Abstract: Progressive familial intrahepatic cholestasis type 3 is caused by biallelic variations of ABCB4, most often ( 70%) missense. In this study, we examined the effects of 12 missense variations identified in progressive familial intrahepatic cholestasis type 3 patients. We classified these variations on the basis of the defects thus identified and explored potential rescue of trafficking-defective mutants by pharmacological means. Variations were reproduced in the ABCB4 complementary DNA and the mutants, thus obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
133
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(137 citation statements)
references
References 39 publications
4
133
0
Order By: Relevance
“…Patient has also heterozygous frequent variant c.523A>G, p.(Thr175Ala) in ABCB4 (highest observed allele frequency: 3.38% in Finnish Population, average allele frequency: 1.06%, Exome Aggregation Consortium). Variant is known to be associated with intrahepatic cholestasis of pregnancy, low phospholipid‐associated cholelithiasis syndrome and has been found in compound heterozygous state in a patient with progressive familial intrahepatic cholestasis . However, variant is without effect of localization or function of ABCB4 protein in in vitro assays and has been found in homozygous state in 11 controls (Exome Aggregation Consortium).…”
Section: Resultsmentioning
confidence: 99%
“…Patient has also heterozygous frequent variant c.523A>G, p.(Thr175Ala) in ABCB4 (highest observed allele frequency: 3.38% in Finnish Population, average allele frequency: 1.06%, Exome Aggregation Consortium). Variant is known to be associated with intrahepatic cholestasis of pregnancy, low phospholipid‐associated cholelithiasis syndrome and has been found in compound heterozygous state in a patient with progressive familial intrahepatic cholestasis . However, variant is without effect of localization or function of ABCB4 protein in in vitro assays and has been found in homozygous state in 11 controls (Exome Aggregation Consortium).…”
Section: Resultsmentioning
confidence: 99%
“…However, current medical therapy is not satisfactory for the majority of patients in the long term. Only recently, cell culture‐based studies demonstrated that a disturbed ABCB4 function in selected missense variants leading to defective membrane trafficking can be restored by treatment with chaperone drugs . In the series, the vast majority of patients harbored missense mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Two other chemical chaperones, 4‐phenylbutyric acid and curcumin, have been recently proposed to rescue ABCB4 variants that impaired traffic . However, the majority of variations affect PC secretion activity of ABCB4, and no pharmacological treatment has been proposed for these mutations yet.…”
mentioning
confidence: 99%